ظاهرة الإمالة وأحكامها عند خاتمة المحققين ابن الجزري - ساكر, لعروسة (University of El-oued, 2018)
الإمالة في عرف اللغويين الميل والعدول، وهي مصدر أملت الشّيء إمالة أي عدلت به إلى غير الجهة التي هو فيها، وكذلك الميلان وتقول: مال الشيء يميل مَيْلاً وممالاً وأمْيالاً وأمال الشيء إمالة فمال Summary: Ibn al-Jazri singled out the voice guidance of the Qur'anic readings recently, and his material was intensified in his books, especially in his books, "The Propagation in the Ten Readings" and "The Preface in the Tajweed," which included a great audio material. What was compared to other books of recitation and recitation. In this intervention we will try to make a clear presentation, God willing, to one of the images and phenomena of voice guidance of the Quranic readings in the writings of Imam Ibn al-Jazri; that is, the imam, and we are not working in this research on linguistic efforts to conclude the interrogators Ibn al-Jazri, Linguistic proverbs such as Sibweh and Khalil Ibn Ahmad al-Farahidi are better than Menhal. Rather, they derived the texts of the phonetic material in a manner consistent with what was said by his teacher, Abu Amr al-Dani, and added something to his own jurisprudence
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج01. ع.02. جامعة الوادي
Keywords: الإمالة , التحقيق